Contemporary trends of preschool education - Kulić Radivoje I.; Partalo Sanja M. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2012)
It is a common fact for the most systems of preschool education that they are all formed under the influence of pedagogical ideas of Comenius, Locke, Rousseau and in a certain way Pestalozzi as a founder of special programs and activities in that area. Although being integrated in the school system, preschool education is not obligatory in the most European countries, not even today. There is a lack of total financial support of the state for the programs of preschool education in such conditions, and that enables the private sector to use that kind of situation and become an alternative in its organization. The novelty is that there are more and more independent preschool institutions which are funded by different organizations, as well as the fact that the institutions of preschool education function as elementary schools in some countries. Generally speaking, there are three types of program in most institutions of preschool education: academic, intellectual and programs of the parents' efficiency that is mostly conditioned by the type of a preschool institution. .